PENDEKATAN LEAN SIX SIGMA DAN TAGUCHI UNTUK MENGATASI MASALAH PENGEMASAN DAN PEMASARAN PRODUK WEDANG UWUH INSTAN SRUPUT - Elly Wuryaningtyas Yunitasari; Emmy Nurhayati (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2017)
Wedang Uwuh Instan Sruput is one of the business unit of Industrial Engineering Program, Faculty of Engineering, Universitas Sarjanawiyata Tamansiswa Yogyakarta. Wedang Uwuh Sruput is an innovative manufacture of wedang uwuh into instant from the original form of whole and raw spices. The resulting product results sometimes have different quality/taste in each production process. The purpose of this research is to improve product quality of Wedang Uwuh Instan Sruput, improve the composition of herb wedang uwuh product, improve the concept of packaging and improve the marketing of the wedang uwuh products. The object of this research is Wedang Uwuh Sruput Prodi Teknik Industri UST. The materials used are instant wedang uwuh maker such as ginger, clove leaf, cinnamon leaf, secang wood, cloves, lemongrass, sugar and water. Identification is done on factors that affect product quality in order to create the same product in the market. The experiment was conducted by performing several times of Wedang Uwuh Sruput production with several variations of composition/formula using Taguchi method to maintain product consistency and quality. In this experiment there are 4 factors(sugar,ginger,water and secang)with 3 level design,that is 2,8 kg;2.9 kg and 3.0 kg for sugar,1.0 kg;1.2 kg and 1.4 kg for ginger,water is 5.0 L;5.2 L and 5.4 L,while the secang is 200 gr,210 gr,220 gr. The difference of the output of Wedang Uwuh Sruput is caused by the difference of sugar content, the difference of ginger content, the difference of the amount of water and the difference of the number of secang used, the use of different raw material specification, the length of production process is not same and the production process is still manual. The result shows that Waste which has the highest weight is waiting with the value of 0.252 at rank 31. Then the calculation of sigma value at early check is at the level of 3,001 sigma and final check at 2,455 sigma level. From the calculation of sigma level can be seen that the level of quality in Business Unit Wedang Uwuh "Sruput" is still far from lean six sigma target. Therefore, the advice given to the Business Unit Wedang Uwuh "Sruput" in the form of corrective actions that have been analyzed in this study. It was found that the most appropriate composition based on consumer preferences was Sugar 2.9 kg;Ginger 1.4;Water 5 L; and Wood Secang 200 gr.